Knowledge-Based and Intelligent Information and Engineering Systems 14th International Conference, KES 2010, Cardiff, UK, September 8-10, 2010, Proceedings, Part III - Setchi, Rossitza; Jordanov, Ivan.; Howlett, Robert J.; Jain, Lakhmi C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The four-volume set LNAI 6276--6279 constitutes the refereed proceedings of the 14th International Conference on Knowledge-Based Intelligent Information and Engineering Systems, KES 2010, held in Cardiff, UK, in September 2010. The 272 revised papers presented were carefully reviewed and selected from 360 submissions. They present the results of high-quality research on a broad range of intelligent systems topics.
Knowledge-Based Systems for e-Business -- Quality Assurance and Intelligent Web-Based Information Technology -- Knowledge-Based Interface Systems -- Reasoning Based Intelligent Systems -- Data Mining and Service Science for Innovation -- Innovations in Chance Discovery -- Advanced Knowledge-Based Systems -- Intelligent Network and Service -- Soft Computing Techniques and Their Intelligent Utilizations Toward Gaming, Robotics, Stock Markets etc. -- Immunity-Based Systems.
Keywords: Computer science; Computer Communication Networks; Database management; Information storage and retrieval systems; Information systems; Artificial intelligence; Optical pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Computer Communication Networks; Information Storage and Retrieval; Pattern Recognition; Database Management